2017
DOI: 10.4049/jimmunol.1700606
|View full text |Cite
|
Sign up to set email alerts
|

CD27-Mediated Regulatory T Cell Depletion and Effector T Cell Costimulation Both Contribute to Antitumor Efficacy

Abstract: CD27, a member of the TNFR superfamily, is constitutively expressed in most T cells and plays crucial roles in T cell effector functions. The costimulation and antitumor activity of CD27 agonistic Abs have been well documented in mouse models. Clinical testing of a human IgG1 anti-CD27 Ab, varlilumab (clone 1F5), is ongoing in cancer patients. In this study, we set out to further understand CD27 as an immunomodulatory target and to address the mechanism of antitumor efficacy using different IgG isotypes of 1F5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 64 publications
1
42
0
Order By: Relevance
“…The therapeutic promise of such neo-epitope peptide vaccines has recently been demonstrated in the setting of advanced melanoma, where the administration of long peptides derived from melanoma neo-antigens has resulted in effective antitumor T cell responses. 40,41 To broaden the scope of this approach, we envision that putatively any class I tumor neo-antigen could be linked to a helper epitope (e.g., P30) and administered alongside adjuvant αhCD27 to enhance its immunogenicity and efficacy, giving rise to a customizable vaccine/adjuvant treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic promise of such neo-epitope peptide vaccines has recently been demonstrated in the setting of advanced melanoma, where the administration of long peptides derived from melanoma neo-antigens has resulted in effective antitumor T cell responses. 40,41 To broaden the scope of this approach, we envision that putatively any class I tumor neo-antigen could be linked to a helper epitope (e.g., P30) and administered alongside adjuvant αhCD27 to enhance its immunogenicity and efficacy, giving rise to a customizable vaccine/adjuvant treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…In murine tumor models, treatment with an anti–CTLA‐4 antibody led to a reduction in the number of intratumoral Tregs and better tumor control . More recently, administration of an anti‐CD27 antibody in mouse tumor models and in patients with advanced solid tumors resulted in antitumor activity associated with T‐cell stimulation and the depletion of Tregs . Hence, alterations in the amount of Tregs may impact the effectiveness of immunotherapy.…”
Section: Mechanisms Of Resistance To Cd3‐bispecific Antibodiesmentioning
confidence: 99%
“…61 More recently, administration of an anti-CD27 antibody in mouse tumor models and in patients with advanced solid tumors resulted in antitumor activity associated with T-cell stimulation and the depletion of Tregs. 62,63 Hence, alterations in the amount of Tregs may impact the effectiveness of immunotherapy. It has been shown that high percentages of Tregs in samples of patients with ALL not responding to blinatumomab treatment was predictive in determining the non response, and the depletion of Tregs in non responding patient samples restored blinatumomab-triggered T-cell proliferation.…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…11,23,24 Antitumor activity was also dependent on the interaction between the mAb and specific Fc gamma receptors (Fc R), implying that in vivo function could be further modulated by generating specific isotypes of the CD27 agonist. 25 A concern of anti-CD27 mAb treatment is the potential for engagement of regulatory T cells that express high levels of CD27 and represent a common cell population in various tumor microenvironments. In fact, in mouse models, persistent activation via the CD27-CD70 signaling pathway has been associated with a significant Treg cell expansion that could be detrimental to antitumor responses.…”
Section: Act or Car T Cell Therapymentioning
confidence: 99%
“…Importantly, Varlilumab only acted on cells that also received a signal through their TCR, ensuring specificity of the treatment, while simultaneously avoiding potentially severe side effects . Antitumor activity was also dependent on the interaction between the mAb and specific Fc gamma receptors (FcγR), implying that in vivo function could be further modulated by generating specific isotypes of the CD27 agonist . A concern of anti‐CD27 mAb treatment is the potential for engagement of regulatory T cells that express high levels of CD27 and represent a common cell population in various tumor microenvironments.…”
mentioning
confidence: 99%